Cervical osteoarthropathy: an unusual cause of dysphagia - Srinivas, P.; George, J. (Oxford University Press, 1999)
PRESENTATION: A 72-year-old man complained of progressive dysphagia for solids associated with a sensation of foreign body in his throat for 2 years. A barium swallow showed a bridging osteophyte between C4 and C5 vertebrae indenting the oesophagus posteriorly and displacing it anteriorly. OUTCOME: He refused surgical intervention and was given dietary advice. After 6 months, his weight was steady and he was able to swallow semi-solid food without difficulty.